Improving the Allocation of Spots in Child Care Facilities for Toddlers in Germany: A Mechanism Design Approach - Sissa Carlsson; Stephan L. Thomsen (Institute for the Study of Labor (IZA), 2015)
The undersupply of spots in German daycare facilities for toddlers challenges parents' possibilities to work. To ease the situation, the government implemented a new law entitling every child between ages one and three to daycare supervision for about four hours per day. Nevertheless, the stressed situation of matching demand and supply does not only result from limited spaces but also from inefficient allocation. By means of simulations under different scenarios, we contrast a stylized version of decentralized allocation to a centralized allocation mechanism which applies a deferred-acceptance algorithm. This centralized system results in better and faster matches.
Keywords: C78; D82; J13; 330; allocation mechanism; deferred-acceptance algorithm; early education; child care